STRATEGI KESANTUNAN NEGATIF TINDAK TUTUR DIREKTIF MASYARAKAT INDONESIA DALAM AKUN TWITTER PRESIDEN JOKO WIDODO - Adzim, Sukron; Djatmika, Djatmika; Sumarlam, Sumarlam (English Department FBS UNP, 2019)
This research aims to describe negative politeness strategy of Indonesians in President Joko Widodo’s twitter account. The type of this research is qualitative descriptive with pragmatic approach. The data source of this research is President Joko Widodo’s twitter on September 2016 focusing on law topic. The data of this research is lingual data as speach act realization in written form. The technique of collecting data uses purposive sampling technique. The analysis model is based on two approaches, which are linguistic approach by Sudaryanto and etnography by Spradley which are domain, taxonomy, componential and cultural themes. There are six negative politeness strategies as this research finding, including indirect strategy, asking strategy, face threatening strategy, nominalization strategy, and straightforward strategy in which each is realized in directive speech act.